'Play the Rain Down': Prince, Paul Morton, and the Idea of Black Ecstasy. Issue 1 (February 2022) - SHELLEY, BRAXTON
Abstract: This article grapples with 'Let It Rain', the title track of Bishop Paul S. Morton and the Full Gospel Baptist Church Fellowship's 2003 release, which revises Michael Farren's contemporary Christian ballad by braiding it together with Prince's 'Purple Rain' and the formal logic of Black gospel tradition. As the Full Gospel version of this song commingles these seemingly discordant components, Morton, choir, and band turn a sung prayer into an assertion of interworldly presence. Building on its received musical materials, this gospel power ballad performs the Black gospel tradition's characteristic inflection – an arresting turn from one level of musicking to a heightened, ecstatic frame. In so doing, this song brings rain near, illuminating the links between performances of musical ecstasy and musical Blackness.